1970
DOI: 10.1002/1097-0142(197006)25:6<1261::aid-cncr2820250603>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Serum alpha-feto-protein and primary cancer of the liver in man

Abstract: Cases with abnormal liver function tests, Bantu blood donors, neonates, Caucasian patients with primary cancer of the liver, and male Bantu mine workers with primary cancer of the liver have been investigated by means of a quantitative alpha‐feto‐protein (AFP) immunodiffusion assay. No false‐positive AFP tests have occurred, and 78% of primary liver cancer patients are positive. More sensitive tests are capable of increasing the positivity rate still further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
7

Year Published

1970
1970
2001
2001

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(39 citation statements)
references
References 11 publications
1
31
0
7
Order By: Relevance
“…7 and 8). McIntire et al, (1975) and Purves et al, (1970) have also reported similar findings in gastrointestinal and hepatic neoplasia. Nonetheless, while rising titres may indicate drug ineffectiveness, clinically observable progressive disease may take place in the absence of changing AFP levels.…”
Section: ···mentioning
confidence: 61%
See 1 more Smart Citation
“…7 and 8). McIntire et al, (1975) and Purves et al, (1970) have also reported similar findings in gastrointestinal and hepatic neoplasia. Nonetheless, while rising titres may indicate drug ineffectiveness, clinically observable progressive disease may take place in the absence of changing AFP levels.…”
Section: ···mentioning
confidence: 61%
“…widely differing amounts (Purves et al, 1970). Plasma levels seem to be unrelated to tumour size; nodular and poorly differentiated tumours tend to be associated with the highest levels (Glazer et al, 1974).…”
Section: ···mentioning
confidence: 99%
“…After birth, the protein level in the serum rapidly decreases. However, under pathologic conditions, AFP is detected in the serum of adults with hepatocellular carcinoma, those with yolk sac tumors, and those with noncancerous liver disease associated with liver regeneration, such as cirrhosis and hepatitis [2][3][4][5][6]. AFPProducing malignant tumors have been reported in several organs; for example, the lung [7,8], pancreas [9,10], Macroscopic type and the depth are according to the Japanese classification of gastric carcinoma [25] NA, details not available; BW, body weight; U, upper-third portion; M, middle-third portion; L, lower-third portion; U 1 , remnant stomach; TG, total gastrectomy; STG, subtotal gastrectomy; DG, distal gastrectomy; PG, partial gastrectomy; GR, gastric resection; LR, liver resection; li, liver; ln, lymph nodes; lu, lung; p, peritoneum; panc, pancreas; om, omentum; 5-FU, 5-fluorouracil; MMC, mitomycin C; ADM, adriamycin; AFP, alpha-fetoprotein; PIVKA-II, des-γ-carboxy prothrombin; CEA, carcinoembryonic antigen; CA 19-9, carbohydrate artigen 19-9; TS-1, 1M tegafur-0.4 M gimestat-1 M ostat potassium; CDDP, cisplatin; 5'DFUR, 5Ј-deoxy-5-fluorouridine; UFT, tegafur uracil; rad 1 , intraoperative radiation therapy; rad 2 , postoperative radiation therapy; died, died of the disease colon [11], bladder [12], and ovary [13].…”
Section: Discussionmentioning
confidence: 99%
“…After birth, the level of the protein in serum rapidly decreases. However, its level is elevated in patients with hepatocellular carcinoma and in those with noncancerous liver diseases associated with liver regeneration, such as cirrhosis and hepatitis [2][3][4][5][6]. Recently, AFP-producing tumors have been reported in several different organs [7][8][9][10][11][12][13], with gastric adenocarcinoma being one of the most common of these tumors [14].…”
Section: Introductionmentioning
confidence: 99%
“…The value of the demonstration of alpha, fetoprotein (a, FP) in the diagnosis of hepatoma is now well established ' (O'Connor, Tatarinov, Abeleve, and Uriel, 1970;Purves, Bersohn, and Geddes, 1970). The technique most commonly used for this purpose is bidimensional immunodiffusion which is simple and practical, but may take up to 72 hours and is not very sensitive.…”
Section: Technical Methodsmentioning
confidence: 99%